Estudio de prefactibilidad para la implementación de un operador logístico de servicios de transporte de productos hidrobiológicos refrigerados - Huaman Correa, Luciana Joseline (2023)
The main objective of this work is to determine the feasibility of installing a logistics operator for refrigerated hydrobiological product transportation services in the department of Ancash. The target market is concentrated in the main fishing terminals of the department of Lima, located in the district of Villa María del Triunfo and the district of Ventanilla. Annual demand is 557 services for the first year and 766 services for the last year of operations. The logistics operator's service capacity is 828 services for the first 3 years and 1 104 services for the last 2 years of the project. The logistics operator's facilities will be located in the city of Santa in the department of Ancash, with a total area of 1 500 m2. The service process includes the loading and unloading of hydrobiological products; therefore, procedures, service quality controls, as well as implements, tools, uniforms, and other necessary items for proper handling are included. The project investment is S/1 823 675 before starting operations and S/223 256 for year 4, and it was determined that financing 65% of the pre-operational investment was more profitable, since the economic and financial flows indicate a recovery period of approximately 1 year and 4 months, and 5 months, respectively. In addition, under financing, an IRR of 102% was determined, higher than the shareholder's opportunity cost of 14,09%, and a positive NPV of S/2 659 796. Finally, the accumulated added value of the project is S/8 662 049. and an investment of S/62 885 for the generation of a job; therefore, its effect is positive on society.